Pooled Analysis of Central Venous Pressure and Brain Natriuretic Peptide Levels in Patients With Extubation Failure - Cao, Jianghong; Wang, Beibei; Zhu, Lili; Song, Lu (Frontiers in Physiology, 2022)
Abstract Purpose: Cardiac insufficiency has been considered to be a common cause of extubation failure. Some studies have shown that central venous pressure (CVP) and brain natriuretic peptide (BNP) are able to predict extubation outcomes. Therefore, we conducted a pooled analysis to evaluate the potential of CVP and BNP levels as predictors of extubation outcomes, using a cohort of critically ill patients who were on mechanical ventilation (MV). Methods: We searched three online electronic databases up to October 2021. All data were analyzed using Review Manager 5.4. For each study, the analysis was performed using standardized mean differences (SMD) with 95% confidence intervals (CI). Results: The pooled analysis of seven studies on CVP levels and extubation outcomes showed that elevated CVP levels were significantly associated with extubation failure (SMD:0.47,95% CI: 0. 43 to 0.51, P < 0.00001). This association also appeared before extubation (SMD:0.47,95% CI: 0. 43 to 0.51, P < 0.00001), but it did not appear after extubation (SMD: 0.63,95% CI: -0.05 to 1.31, P＝0.07). Similarly, pooled analysis of eight studies on BNP levels and extubation outcomes showed that increased BNP levels are closely related to extubation failure (SMD:0.68,95% CI: 0.49to 0.86, P < 0.00001). This relationship also occurs before (SMD: 0.57,95% CI: 0.35 to 0.79, P < 0.00001) and after (SMD: 0.91,95% CI: 0.59 to 1.23, P < 0.00001) extubation. Conclusions: This study showed that elevated CVP and BNP levels are associated with extubation failure in critically ill patients. However, BNP levels are more valuable than CVP levels in predicting extubation outcomes.